Physiological quality of maize seeds treated and stored at different temperatures - Santos, Alessandra Libério dos; Senen, Sabrina de Cassia; Pereira, Laís Fernanda Melo (Revista de Ciências Agroveterinárias, 2025)
Treatment of corn seeds is a common practice in seed processing units since the productive success of crops depends on the use of high-quality seeds. The control of deterioration in storage ensures the maintenance of the germination capacity and vigor of the seeds, allowing them to tolerate adverse factors when sown in the field. The objective of this study was to analyze the quality of corn seeds treated and stored at different temperatures. Corn seeds of AL Bandeirante variety were subjected to chemical treatment with insecticides (based on Actellic 500 CE + K-obiol + Maxim X) and stored at temperatures of 10°C, 18°C and 26°C. At 0, 30, 60 and 90 days, seed performance was evaluated in split-plots in time with four replications by means of moisture content, germination percentage, sand emergence percentage and accelerated aging test. The percentage of seed germination remained within the commercialization standards for up to 90 days of storage at temperatures of 10ºC, 18ºC and 26ºC. However, the evaluation of vigor from the percentage of seedling emergence and percentage of germination after accelerated aging reduced with the advance of seed conservation, indicating changes in vigor due to storage temperature.